Paper-Based Characteristics of Oil Palm Empty Fruit Bunch and Waste Paper - Endah Andarini; Ainun Rohanah; Saipul Bahri Daulay (Universitas Sumatera Utara, 2013)
Every year the need for paper continue to rise while the raw material from wood have been harder to find, therefore and the alternative of raw materials would be of plant fibers or fibrous waste such as empty fruit bunches of oil palm and paper waste. This research was aimed to study the characteristics of paper made ​​from empty fruit bunch pulp and paper waste pulp. Therefore, a research had been conducted in May-June 2013. The making of paper was done at Jl. Roso No. 8 Delitua and the testing of paper was done in PT PDM Indonesia Laboratory, Medan North Sumatera using factorial randomized block design with one factor i.e. waste paper composition (0%, 10%, 20%, 30%, 40% and 50%). Parameters observed were grammage, tensile and tearing strength. The results showed that the composition of the waste paper had highly significant effect on grammage and tensile strength. The resulting paper could be categorized as art paper with the best results obtained from the composition of 40% (120 g of oil palm empty fruit bunches and 80 g waste paper). Keywords: oil palm empty fruit bunches, waste paper, pulp composition, paper.